2018
DOI: 10.1182/blood-2018-99-114668
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Ixazomib, Daratumumab and Low Dose Dexamethasone (IDd) in Unfit and Frail Newly Diagnosed Multiple Myeloma (NDMM) Patients; First Interim Safety Analysis of the Phase II HOVON 143 Study

Abstract: Introduction Data from clinical trials indicate that elderly non-transplant eligible newly diagnosed multiple myeloma (nte-NDMM) patients also benefit from novel therapies. However, overall survival is inferior in unfit and frail compared to fit patients as defined by the International Myeloma Working Group (IMWG) frailty index, caused by a high discontinuation rate due to toxicity. Therefore, there is a need for less toxic treatment for unfit and frail patients. In view of the favorable safety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
9
0
1
Order By: Relevance
“…Maintenance therapy until progression or for maximum of 2 years included daratumumab plus ixazomib. Results of the 65 frail patients enrolled in the study (median age 81 years, range 70–92 years) have been recently presented at the last European Hematology Association (EHA) Congress ( 30 ). Overall response rate, primary endpoint, was 78% with 36% of the patients achieving at least a VGPR.…”
Section: Transplant-ineligible Newly Diagnosed Multiple Myeloma Patiementioning
confidence: 99%
“…Maintenance therapy until progression or for maximum of 2 years included daratumumab plus ixazomib. Results of the 65 frail patients enrolled in the study (median age 81 years, range 70–92 years) have been recently presented at the last European Hematology Association (EHA) Congress ( 30 ). Overall response rate, primary endpoint, was 78% with 36% of the patients achieving at least a VGPR.…”
Section: Transplant-ineligible Newly Diagnosed Multiple Myeloma Patiementioning
confidence: 99%
“…Similarly, single-agent ixazomib maintenance has been utilized following ixazomib-based induction in four phase 1/2 studies 45,[80][81][82][83] ; a pooled analysis of maintenance patients from these studies reported deepening responses in 23% of patients, as well as a median PFS of 21.4 months and a 3-year OS of 82% from the start of maintenance, with limited new-onset AEs 84 . Ixazomib-daratumumabdexamethasone followed by ixazomib maintenance is being evaluated in unfit and frail patients in the phase 2 HOVON-143 study, which has reported promising safety and response data for the induction phase 85 . However, in the randomized phase 2 HOVON-126/NMSG21#13 trial, in which patients received ixazomib-thalidomidedexamethasone induction and were then randomized to ixazomib or placebo maintenance 86 , preliminary data showed no response or PFS benefit with ixazomib maintenance to date, although ixazomib did not result in additional toxicity compared to placebo ( Table 6).…”
Section: Maintenance Therapy Post-induction In the Nontransplant Settingmentioning
confidence: 99%
“…Updated efficacy results are awaited. 40 Ongoing trials of daratumumab-based combinations in transplant ineligible NDMM patients are listed in Table 1. 41…”
Section: Daratumumab In Transplant-ineligible Ndmmmentioning
confidence: 99%